The Square Kilometre Array Epoch of Reionisation and Cosmic Dawn Experiment - Trott, Cathryn (2017)
© 2018 International Astronomical Union. The Square Kilometre Array (SKA) Epoch of Reionisation and Cosmic Dawn (EoR/CD) experiments aim to explore the growth of structure and production of ionising radiation in the first billion years of the Universe. Here I describe the experiments planned for the future low-frequency components of the Observatory, and work underway to define, design and execute these programs.